Ca2+ plays an antiviral role by increasing p53 expression to achieve protection against spring viraemia of carp virus infection. Issue 102 (July 2020) - Lu, Long-Feng; Zhou, Xiao-Yu; Zhang, Can; Li, Zhuo-Cong; Chen, Dan-Dan; Zhang, Yong-An; Li, Shun
Abstract: Calcium (Ca) is a messenger that regulates a multitude of physiological processes, but its functions in antiviral progress remain undefined. In this study, we found that Ca 2+ enhances fish survival to defend against spring viraemia of carp virus (SVCV) infection by reversing the instability of p53 mediated by the viral protein. First, Ca 2+ significantly protected cells and fish against SVCV infection by inducing early apoptosis. Additionally, p53 expression, which was inhibited by SVCV N protein, was upregulated by Ca 2+ treatment. Then, the mechanism underlying the reduction of K63-linked p53 ubiquitination by SVCV N protein via the K358 site was completely prevented by Ca 2+ . These findings reveal the role of Ca 2+ in lower vertebrates in the antiviral response, which is connected to and corresponds with viral immune evasion, providing a solution to fish diseases caused by pathogens. Highlights: Ca 2+ significantly strengthens the survival of cells and fish to defend against SVCV infection. Ca 2+ blunts the expression of viral genes and induces the expression of fish p53. Ca 2+ treatment rescues the reduced K63-linked ubiquitination of p53 which degraded by SVCV N protein.